(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Through this research, we studied the effect of the aqueous extract of the caper plant on the process of preparing silver nanoparticles with properties. The method was done by adding the aqueous extract of the caper plant with a concentration of 100ppm to three test tubes containing 10ml of silver nitrate in different sizes (1ml, 2ml, 3ml) and shaking them. For 5 minutes and left for an hour, a gradual brown color was observed indicating the presence of silver nanoparticles. That is, silver nanoparticles were obtained in a fast, safe, inexpensive and very effective way, which makes this method important because silver nanoparticles have wide applications in all fields, which is of great economic and scientific importance